2017
DOI: 10.1002/jcb.25858
|View full text |Cite
|
Sign up to set email alerts
|

Link Between ER-Stress, PPAR-Alpha Activation, and BET Inhibition in Relation to Apolipoprotein A-I Transcription in HepG2 Cells

Abstract: Activating transcription factor peroxisome proliferator-activated receptor alpha (PPARα) may increase apoA-I transcription. Furthermore, Bromodomain and Extra-Terminal domain (BET) protein inhibitors increase, whereas Endoplasmic Reticulum (ER) stress decreases apoA-I transcription. We examined possible links between these processes as related to apoA-I transcription in HepG2 cells. JQ1(+), thapsigargin, and GW7647 were used to induce, respectively BET inhibition, ER-stress, and PPARα activation. Expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 40 publications
(57 reference statements)
8
19
0
Order By: Relevance
“…ApoA-I mRNA expression in HepG2 cells was lower under inflammatory conditions as compared to normal conditions ( Figure 1 ). In agreement with our previous studies [ 15 ], the positive control JQ1(+) and the negative control thapsigargin (Thap) respectively increased and decreased ApoA-I mRNA expression (both p < 0.001). Also, under inflammatory conditions, JQ1(+) significantly ( p < 0.001) increased ApoA-I gene expression, whereas Thap even further decreased ApoA-1 gene expression ( p < 0.001) compared with the normal condition ( Figure 1 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…ApoA-I mRNA expression in HepG2 cells was lower under inflammatory conditions as compared to normal conditions ( Figure 1 ). In agreement with our previous studies [ 15 ], the positive control JQ1(+) and the negative control thapsigargin (Thap) respectively increased and decreased ApoA-I mRNA expression (both p < 0.001). Also, under inflammatory conditions, JQ1(+) significantly ( p < 0.001) increased ApoA-I gene expression, whereas Thap even further decreased ApoA-1 gene expression ( p < 0.001) compared with the normal condition ( Figure 1 ).…”
Section: Resultssupporting
confidence: 92%
“…All together, these results of C4 suggested that PPARα transactivation might be involved in the effects of SCFAs on ApoA-I expression in normal and inflammatory conditions. This is also in agreement with our previous study in which we found a clear role for PPARα transactivation on ApoA-I mRNA transcription in non-inflamed HepG2 cells [ 15 ]. Moreover, it seems that BET inhibition does not contribute to the effects of SCFAs on ApoA-I during inflammatory conditions, since KEAP1 was not reduced in inflamed HepG2 cells.…”
Section: Discussionsupporting
confidence: 94%
“…HepG2 cells were grown in MEM supplemented with 10% FCS, sodium pyruvate and non-essential amino acids and pen/strep as described [18]. Collection and differentiation of human primary myotubes have been described previously [19].…”
Section: Cell Culturementioning
confidence: 99%
“…Because of this hallmark, BAT has been coined an important target to combat metabolic disease [12,13]. With respect to lipid metabolism, BAT stimulation via cold exposure in humans specifically showed uptake of the FFA tracer 18 F-FTHA which was not observed in WAT or muscle [14]. Cold-exposed mice subjected to an oral lipid tolerance test, did not show changes in TG concentrations due to active BAT [15].…”
Section: Introductionmentioning
confidence: 99%
“…3 ). As the reduction of PPARα expression may inhibit ERS ( 12 ), the level of ERS was tested. During ER stress, the level of CHOP expression is elevated and its role in programmed cell death of ER-stressed cells is correlated with its role in promoting protein synthesis and oxidative stress inside the ER ( 13 ).…”
Section: Resultsmentioning
confidence: 99%